Pengaruh Sustainability Reporting, Profitabilitas, Struktur Modal Dan Insentif Manajer Terhadap Nilai Perusahaan - Yolanda Pratami; Poppy Camenia Jamil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Indonesia's growing economy require every company to improve company performance for achievement of company goals. In addition, the company is also expected to increase the firm’s value for shareholder prosperity. Firm’s value is very important because it shows the performance of the company that can affect investor perceptions of the company. The issue of companies listed on the Indonesia Stock Exchange shows that most firm’s values ​​have declined from 2017 to 2018 while good company values ​​are seen from stable and rising share prices. This study aims to test empirically the influence of sustainability reporting, profitability, capital structure and managerial incentive to firm’s value on the companies listed in Indonesia Stock Exchange during periode 2017-2018. This study used purposive sampling method for the selection of sampel. The population of this research is 613 companies with total sample of 39 companies. Data analysis technique in this research is multiple regression analysis with SPSS version 23.0. The research result show that sustainability reporting has no effect to to the firm’s value, profitability has effect to the firm’s value, capital structure has no effect to the firm’s value and managerial incentive has no effect to the firm’s value. The results of this study are expected to be a motivation for company management to increase firm’s value because it will have an impact on investor interest in investing in companies in Indonesia. Keywords: Sustainability Reporting, Profitability, Capital Structure, Managerial Incentive, Firm’s Value